Analisis Kinerja Keuangan Pemerintah Daerah Provinsi Jawa Timur Sebelum Dan Saat Pandemi Covid-19 - Bunga Qolbiyah Syahara; Muhammad Aufa (Universitas Muhammadiyah Gresik, 2022)
This study aims to analyze the financial performance of the East Java Provincial Government before and during the Covid-19 pandemic. The object of this research is the Regional Government in East Java. This study uses a comparative quantitative research approach. The type of data used is documentary data and the data source used is secondary data. The population used in this study were 38 LKPDs in East Java Province which had been audited by the East Java BPK and statistical data from the East Java BPS. While the sampling technique using a saturated sampling technique. The data analysis technique used is descriptive statistics, normality test and different test. Based on the data analysis carried out, it was concluded that there were significant differences in financial independence, financial flexibility, operational solvency and no significant differences in short-term solvency, long-term solvency, solvency services of the East Java Provincial Government before and during the Covid-19 pandemic.